New Life of the Maisky’s Diary - V. Pechatnov (Сравнительная политика)
Book Review: The Maisky Diaries: Red Ambassador to the Court of St James’s, 1932-1943 / Ed. by Gabriel Gorodetsky. Yale University Press: New Haven and London, 2015. 584 p.